RAINFALL VARIABILITY IN GUNUNGSEWU KARST AREA, JAVA ISLAND, INDONESIA - Cahyadi, Ahmad; Haryono, Eko; Nugroho Adji, Tjahyo; Widyastuti, Margaretha; Agus Riyanto, Indra; Taufiq Nur Muhammad, Dzakwan; Fattah Tastian, Naufal (Indonesian Journal of Forestry Research, 2021)
Karst area is highly susceptible to changes to climate parameters. One of the parameters is rainfall variability. In addition to shaping the condition of water resources, rainfall in the Gunung Sewu karst area determines the nature of crop and livestock of the agriculture sectors―the local population's main economic activities, warranting the significance of the rainfall variability studies. Rainfall variability in karst areas also affects disaster conditions such as drought and floods. However, due to insufficient meteorological data in quality and quantity, there has been no rainfall variability studies conducted in this locality. The research intended to analyze rainfall variability in the Gunung Sewu karst area in 1979‒2013 by utilizing rainfall predictions from satellite images that many scholars had tested in different locations and recognized as having good quality. In the analysis, mean monthly rainfall was calculated, and the trends of annual rainfall and average rainfall intensity, dry and rainy seasons, the number of rainy days, and the effect of ENSO (El Niño Southern Oscillation) on rainfall were analyzed. The research data were 35 years of daily rainfall records derived from the National Centers for Environmental Prediction (NCEP) Climate Forecast System Reanalysis (CFSR). The analysis results showed that the mean rainfall, number of rainy days, and rainfall intensity had an increasing trend. Also, El Niño quantitatively influenced the rain in the Gunung Kidul karst area.